Investigation of the Causes of the Longitudinal and Solar Cycle Variation of the Electron Density in the Bering Sea and Weddell Sea Anomalies. Issue 9 (17th September 2018) - Richards, P. G.; Meier, R. R.; Chen, Shihping; Dandenault, P.
Abstract: This paper investigates and quantifies the longitudinal, solar cyclical, and diurnal variation of the ionosphere peak electron density observed by six ionosondes located between 18 and 151°E near 60°N. Embedded within this region is the Bering Sea anomaly (BSA) where the midnight peak electron density exceeds the midday peak electron density in summer. The BSA is a region West of Alaska extending from approximately 100° to 200° east geographic longitude and 55° to 70° north geographic latitude at its widest. By comparing a physical model with ionosonde data from the 1970s and 1980s, it is found that longitudinal changes in the neutral winds and neutral densities are the most likely explanation for the electron density variation between 18 and 151°E near 60°N. Longitudinal differences in magnetic declination and inclination are small and have a negligible effect on the electron density behavior. Our definition of and the behavior of the BSA are analogous to the Weddell Sea anomaly (WSA), a region in the Southern Hemisphere where the midnight peak electron density also exceeds the midday peak electron density in summer. Although the overall BSA electron density is a factor of 2 smaller than that in the WSA, the two anomalies have similar midnight to midday electron density ratios. It is found that the BSA gets stronger with increasing solar activity, while the WSA gets weaker. It is also demonstrated that including vibrationally excited N2 in an ionosphere model is crucial for producing the observed midnight to midday electron density ratios. Key Points: The longitudinal variation of the Bering Sea Anomaly (BSA) electron density is caused by variations in both the neutral densities and the neutral winds The magnetic field configuration is only a minor factor in the longitudinal variation of the electron density in the BSA Vibrationally excited N2 plays an important role in the midnight to midday electron density ratio